Antiferroelectric Tunnel Junctions. (15th May 2017) - Apachitei, Geanina; Peters, Jonathan J. P.; Sanchez, Ana M.; Kim, Dong Jik; Alexe, Marin
Abstract : Antiferroelectric tunnel junctions of La0.7 Sr0.3 MnO3 /PbZrO3 /Co fabricated by pulsed laser deposition and sputtering are reported for the first time. The current–voltage curves highlight the monostability type (threshold) resistive switching corresponding to the antiferroelectric behavior for the PbZrO3 barrier down to ≈4 nm thickness. Tunneling electroresistance values up to 10 9 %, which is much higher than the usual values in ferroelectric tunnel junctions, are observed at room temperature. The resistive switching is attributed to a combination of the nonpolar to polar switching induced by an external field, leading to significant changes in the barrier heights, and the crossover from direct tunneling to Fowler–Nordheim tunneling. At low temperatures, the devices exhibit an inverse tunneling magnetoresistance, in which the resistance is higher in the parallel magnetization state, most probably caused by interfacial Zr and Co ions' hybridization influence on the spin polarization. Abstract : Antiferroelectric tunnel junctions of La0.7 Sr0.3 MnO3 /PbZrO3 /Co are reported for the first time, exhibiting monostability type (threshold) resistive switching corresponding to the antiferroelectric behavior for PbZrO3 barrier with tunneling electroresistance values up to 10 9 %. The resistive switching is attributed to a combination of the nonpolar to polar switching induced by an external field and the crossover from direct to Fowler–Nordheim tunneling.